Green Logistics Implementation Factors: A Study on a Global Logistics Provider - Lew, A.F.R.; Chew, B.C.; Hamid, S.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Green logistics has become the newest trend in doing business that is not just economy sustainable but is also environment sustainable. As the world ecology is becoming worse due to globalization and industrialization with the rising temperature and sea levels, many logistics companies are applying green logistics as it helps mitigate climate change by reducing carbon emissions. This paper identified and analyzed the internal and external factors in implementing green logistics. In this case study, a global logistics company which is DB Schenker Malaysia was chosen as the research location. Qualitative data were obtained through various literatures and through 30 semi-structured open-ended interviews. This study found that there are four internal implementation factors and three external implementation factors in green logistics. The four internal factors are cost efficiency, human resource skills, knowledge and supports, information technology and system, and organization’s/top management support. Meanwhile, the three external factors are public and consumers’ pressures, competitions, and collaboration and integration with suppliers and partners. Findings also indicated that implementing green logistics has many benefits but only a few implementation factors found in the literatures were relevant to DB Schenker Malaysia. Nonetheless, the company still implements green logistics in order to be a top logistics company.